2012
DOI: 10.1186/1550-2783-9-3
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional behavior of cyclists during a 24-hour team relay race: a field study report

Abstract: BackgroundInformation about behavior of energy intake in ultra-endurance cyclists during a 24-hour team relay race is scarce. The nutritional strategy during such an event is an important factor which athletes should plan carefully before the race. The purpose of this study was to examine and compare the nutritional intake of ultra-endurance cyclists during a 24-hour team relay race with the current nutritional guidelines for endurance events. Additionally, we analyzed the relationship among the nutritional an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 48 publications
1
20
1
Order By: Relevance
“…In the current study, CHO intake accounted for 57% of total EI, which is in the range of values reported for the team-event of RAAM (56 to 64%, Hulton et al, 2010). Higher relative CHO intakes (70 to 75% of EI) have been reported in single-case studies during the RAAM and the Race Across the Alps (Knechtle et al, 2005;Bircher et al, 2006 and in bike races of shorter duration (Black et al, 2012;Bescós et al, 2012). Consequently, fat intake in the current study (29.3 ± 4.0%) was considerably greater than fat intake reported in other ultra-endurance events.…”
Section: Macronutrientscontrasting
confidence: 44%
See 1 more Smart Citation
“…In the current study, CHO intake accounted for 57% of total EI, which is in the range of values reported for the team-event of RAAM (56 to 64%, Hulton et al, 2010). Higher relative CHO intakes (70 to 75% of EI) have been reported in single-case studies during the RAAM and the Race Across the Alps (Knechtle et al, 2005;Bircher et al, 2006 and in bike races of shorter duration (Black et al, 2012;Bescós et al, 2012). Consequently, fat intake in the current study (29.3 ± 4.0%) was considerably greater than fat intake reported in other ultra-endurance events.…”
Section: Macronutrientscontrasting
confidence: 44%
“…Consequently, fat intake in the current study (29.3 ± 4.0%) was considerably greater than fat intake reported in other ultra-endurance events. In most studies, fat intake was in the range between 14 and 17% of total EI (Bescós et al, 2012;Hulton et al, 2010;Bircher et al, 2006;Knechtle et al, 2005).…”
Section: Macronutrientsmentioning
confidence: 97%
“…It has been reported before, that the cycling speed during the training units was significantly and negatively related to race time (Knechtle et al, 2011, 2012b). Nevertheless, differences in race performances in ultra-endurance events can also result from various other influencing factors like race tactics, weather conditions, motivation (Lahart et al, 2013), sleep deprivation (Knechtle et al, 2012a), nutrition (Stewart and Stewart, 2007; Hulton et al, 2010; Bescós et al, 2012; Lahart et al, 2013; Paulin et al, 2015) and so on, which are not taken into account in this publication.…”
Section: Discussionmentioning
confidence: 99%
“…This cross-sectional data analysis is limited since aspects such as anthropometry [40,41], physiology [42], training [17,40,41], previous experience [17,43], pacing strategy [42,44], nutrition [3,18,45], fluid intake [46,47], and support during the race [17,40,41] were not included. Another weak point is the fact that the analysis is based on publicly available data, without any explanatory variables.…”
Section: Discussionmentioning
confidence: 99%